A Comparison of the Performances of Different Mesoporous Titanias in Dye-Sensitized Solar Cells. (27th May 2015) - Latini, Alessandro; Panetta, Riccardo; Cavallo, Carmen; Gozzi, Daniele; Quaranta, Simone
Abstract : The present work aims at optimizing titanium dioxide morphology for dye-sensitized solar cells applications. Five different anatase phase mesoporous titanias were prepared and tested as photoanodes in dye-sensitized solar cells. The materials were prepared by using a template approach. Two materials were synthesized by using monodisperse silica nanospheres and the other three using two different organic templating agents (Pluronic P123 and Brij 58). A complete characterization of the obtained materials was performed by powder XRD, FEG-SEM, UV-Vis reflectance spectroscopy, BET surface area measurements, and TG-DTA. Several cells were assembled using N719 as dye and a nonvolatile electrolyte based on benzonitrile. The cells were tested by means of J-V curves under simulated solar radiation, IPCE, and dark current measurements. The highest efficiencies were achieved with titania prepared by using Pluronic P123 as template (η max = 6.8 %), while the lowest efficiencies were recorded with using titania samples prepared with the silica nanospheres template (η min = 5.7 %). The different performances of the samples are examined and discussed.